Three new species of Diplocirrus Haase, 1915 (Polychaeta: Flabelligeridae) from Campos Basin in SE Brazil - Teixeira, Juliana Henrique; Rizzo, Alexandra Elaine; Santos, Cinthya Simone Gomes (Zootaxa, 2015)
Currently, 16 species of Flabelligeridae have been recorded in Brazil, four in the genus Diplocirrus: D. glaucus Malmgren, 1867 from Ubatuba, D. capensis Day, 1961 from Santos (São Paulo State) and Diplocirrus sp. from off north of Rio de Janeiro. Diplocirrus glaucus australis Nonato, 1981 is considered a nomen nudum. In the present study, three new species are described: Diplocirrus rugosus sp. nov., Diplocirrus salazarvallejoi sp. nov. and Diplocirrus acafi sp. nov., all collected from soft bottoms off southeast Brazil. A key to all Diplocirrus species is provided.
World Polychaeta Database (WPolyDb). Article is not open access